Semi-Markov reliability models - Raskin, Lev; Sviatkin, Iaroslav; Ivanchikhin, Yuriy; Korsun, Roman (Національний технічний університет "Харківський політехнічний інститут", 2022)
Traditional technologies for reliability analysis of semi-Markov systems are limited to obtaining a stationary state probability distribution. However, when solving practical control problems in such systems, the study of transient processes is of considerable interest. This implies the subject of research - the analysis of the laws of distribution of the system states probabilities. The goal of the work is to obtain the desired distribution at any time. The complexity of the problem solving is determined by the need to obtain a result for arbitrary distribution laws of the duration of the system's stay in each state before leaving. An easy-to-implement method for the analysis of semi-Markov reliability models has been suggested. The method is based on the possibility of approximating probability-theoretic descriptions of failure and recovery flows in the system using the Erlang distribution laws of the proper order. The developed computational scheme uses the most important property of Erlang flows, which are formed as a result of sieving the simplest Poisson flow. In this case, the semi-Markov model is reduced to the Markov one, which radically simplifies the analysis of real systems.

Традиційні технології аналізу надійності напівмарківських систем обмежуються одержанням стаціонарного розподілу ймовірностей станів. Проте, під час вирішення практичних завдань управління у таких системах значний інтерес має дослідження перехідних процесів. Звідси випливає предмет дослідження – аналіз законів розподілу ймовірностей станів системи. Метою роботи є отримання розподілу на будь-який момент часу. Складність розв'язання поставленого завдання визначається необхідністю отримання результату для довільних законів розподілу тривалості перебування системи в кожному стані до догляду. Запропоновано простий у реалізації метод аналізу напівмарківських моделей надійності. Метод заснований на можливості апроксимації теоретико-імовірнісних описів потоків відмов та відновлення в системі за допомогою законів розподілу Ерланга належного порядку. Розроблена обчислювальна схема використовує найважливішу властивість потоків Ерланга, що формуються в результаті просіювання найпростішого пуассонівського потоку. При цьому напівмарківська модель редукується до марківської, що радикально полегшує процедуру аналізу реальних систем.
Напівмарківські моделі надійності
Keywords: semi-Markov reliability models; approximation by Erlang distributions of the proper sequence; напівмарківські моделі надійності; апроксимація розподілами Ерланга належного порядку